(3QSGdI aj ESJNQGL NW fUa GdfgGQs - (3GHf jhfS GdeUQjs ((3CMeO Hf GHQGgje GdSWMi s)
(3ChdgG (B:s
(3bGd Hf jhfS GdeUQi QMeg Gddg HRjGOg CdaGX jMJGL EdjgG ZPG GQOJ Cf JSJNQL NW fUa GdfgGQ HGdEQJaGY GdPi SeJg SJhf aGQUOg Ke VY ebjGSkG eMOOkG s
(3BNQgG (B:s
(3Cf jbSe hLgg HYTQg GLRGA eKdkG hjLYd LfHg efgG NeSI hfUa gPG GdPi hbY Ydjg GdEUWdGM ef Cgd GdUfGYI hGdgd JYGdi Gdehab JeJ GdeSGFd HMeO Gddg JYGdi hYhfg hMSf Jhajbg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B6s
(3HgG CTcGd hQShe gfOSjIs
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3GdGeHQhRjGfG s
Keywords: (3Gdadcs